The Effect of Curry Leaves (Murayya Koenigii L.) on Blood Glucose Levels In Alloxan Diabetic Mice (Mus Musculus) - Fauziah Fauziah; Nindya Nika Putri; Firdus Firdus (Universitas Syiah Kuala, 2014)
This study was conducted to determine the effect of ethanol extract of curry leaves (Murraya koenigii L.) on blood glucose levels in alloxan diabetic mice (Mus musculus). The diabetic conditions were made by giving alloxan 75 mg/kg body weight (BW) and the hypoglycemic effects of extract of curry leaves given with various doses. This study used 24 male mice strain Balb/c in four groups of treatment with six replications, namely the negative control group, the ethanol extract of curry leaf tree 50% mL/10g body weight group, 70% mL/10g body weight group and 90% mL/10g body weight group. The treatment was given orally by using a gastric sonde for 14 days. Blood samples were taken through the sinus caudalis using a scissors. Blood glucose level was measured at 1st , the 8th and the 24th of treatment using blood glucose test strips and Nesco® Multicheck apparatus. Blood glucose data were analyzed by one way ANOVA (Analysis of Variants) and followed by Tuckey test at significance level of 5%. The result showed that treatment of ethanol extract of curry leaves (Murraya koenigii) at various doses significantly affected the decrease on blood glucose levels of mice (Mus musculus) alloxan diabetic.